2017
DOI: 10.1002/mrm.26968
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of the downfield part of 1H MR spectra of human brain at 9.4 T: Magnetization exchange with water and relation to conventionally determined metabolite content

Abstract: Using ultrahigh field allowed improved separation of peaks in the 8.2 to 8.5 ppm amide proton region, and the exchange rates of multiple downfield resonances including the 5.8-ppm peak, previously tentatively assigned to urea, were measured in vivo in human brain. Downfield peaks consisted of overlapping components, and largely missing correlations between upfield and downfield resonances-although not conclusive-indicate limited contributions from metabolites present upfield to the downfield spectrum. Magn Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(91 citation statements)
references
References 43 publications
(69 reference statements)
9
75
0
Order By: Relevance
“…A similar statement can be made for a comparison to the MC‐STEAM spectra obtained at 9.4 T, where again the major exchange‐affected resonances are less prominent than in the current results. Other differences with respect to the nWS 9.4T spectra 16 concern the 7.8ppm resonance (mostly NAA), which is much broader at low field. Also, the peaks further upfield (at 5.8, 6.1 and 6.3 ppm) are much less prominent in the I‐CSE spectra, although that is likely just due to the excitation profile and possibly also an effect of artifacts arising from imperfect water cancelation in MC and residual water excitation with I‐CSE.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar statement can be made for a comparison to the MC‐STEAM spectra obtained at 9.4 T, where again the major exchange‐affected resonances are less prominent than in the current results. Other differences with respect to the nWS 9.4T spectra 16 concern the 7.8ppm resonance (mostly NAA), which is much broader at low field. Also, the peaks further upfield (at 5.8, 6.1 and 6.3 ppm) are much less prominent in the I‐CSE spectra, although that is likely just due to the excitation profile and possibly also an effect of artifacts arising from imperfect water cancelation in MC and residual water excitation with I‐CSE.…”
Section: Discussionmentioning
confidence: 96%
“…STEAM with its intrinsic two‐fold signal loss allowed to reach a TE of 8 ms (13 ms in Ref. 16), but included a longish TM period (~50 ms), with mixing of magnetization between metabolites and water. The semi‐LASER implementation had the disadvantages of longer TE (24 ms in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the different results from other MRSI studies, our results were in agreement with single‐voxel studies that showed a slight increase in creatine for non‐water‐suppressed spectroscopy that could be a result of the chemical exchange effect in water‐suppressed spectroscopy. Even though only upfield metabolites were studied in this work, same methodology can be used in future on the downfield metabolites to validate chemical exchange saturation transfer (CEST) studies .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study at 9.4 T required a larger voxel size (2 × 2 × 3 cm 3 ) for 96 averages in order to achieve good SNR because the study used MC-STEAM localization. 2 However, the current study used an MC-semiLASER sequence, which resulted in good SNR from a smaller voxel (2 × 2 × 2 cm 3 ). As expected, the SNR of the peaks in Figure 1 decreased as the signal decayed exponentially with increasing TEs.…”
Section: Spectral Qualitymentioning
confidence: 99%